2019
DOI: 10.1097/md.0000000000016747
|View full text |Cite
|
Sign up to set email alerts
|

Extranodal natural killer/T-cell lymphoma nasal type with central nervous system involvement mimicked tuberculous meningitis

Abstract: Rationale: Neurologic deficits are rare in patients with extranodal natural killer/T-cell lymphoma (NKTL), nasal type. We present a case that was initially suspected as tuberculous meningitis, but later diagnosed as central nervous system metastasis of NKTL, nasal type, which has never been published previously. Patient concerns: A 55-year-old Chinese man presented with persistent headache and fever. The initial head computed tomography and magnetic resonance imaging (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Regarding the previously reported CNS ENKL outcomes, survival of 1.5 years from the diagnosis is one of the best published results. Previous cases and small studies have shown survival of only 3–6 months when ENKL presents with CNS involvement ( 3 , 4 ). These reports used chemotherapy as the main treatment approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the previously reported CNS ENKL outcomes, survival of 1.5 years from the diagnosis is one of the best published results. Previous cases and small studies have shown survival of only 3–6 months when ENKL presents with CNS involvement ( 3 , 4 ). These reports used chemotherapy as the main treatment approach.…”
Section: Discussionmentioning
confidence: 99%
“…Extranodal natural killer/T-cell lymphoma (ENKL), nasal type, is a rare subtype of mature T and natural killer cell lymphomas which is associated with Epstein-Barr virus (EBV) ( 1 ). ENKL comprises only 1% of all lymphomas in Western countries ( 2 ), and only 3% of all ENKL cases are associated with central nervous system (CNS) involvement ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…ENKTL is one of the most lethal lymphoid malignancies with extremely poor prognosis especially in advanced cases. Although metastasis is often seen in advanced ENKTL that may involve masculine organ and central nervous system [ 31 , 32 ], currently very few studies have explored the underlying mechanisms rendering ENKTL metastasis.…”
Section: Discussionmentioning
confidence: 99%